Prevalence, Awareness, Treatment and Control of Hypertension Among the People Above 15 Years in Rural Area Nagpur Maharashtra - A Cross Sectional Study - Bhardwaj , Sumit D; Sinha , Umesh; Shewte , Mamta K; Khadse , Jyoti R; Bhatkule , Prakash R (National Journal of Community Medicine, 2012)
Introduction: High blood pressure (BP) is a major risk factor for cardiovascular disease and better control can lead to prevention of 300,000 of the 1.5 million annual deaths from cardiovascular diseases in India. Objective: - To evaluate the prevalence, awareness, treatment and control of hypertension among rural population of Maharashtra. Method:-The study involved a survey of 1964 male and 1807 female respondents, aged 15 years and above. Multistage sampling was used for recruitment (PHCs/ sub-centres/ villages). All households in the selected villages were covered and all subjects above 15 years in the household were interviewed.JNC VII criteria was used for labelling a person as hypertensive. Findings: - The overall prevalence of hypertension (JNC VII criteria) was 15.4 % (95% CI 13.2% - 16.4%) among men and 15.9 % (95% CI 14.1 % - 17.6%) among women. Among study subjects who had hypertension, 14.5% were aware of their condition, 9.4 % were taking anti-hypertensive medications, but only 3.9 % achieved the level established by the (JNC VII)/WHO criteria. Conclusions: - We observed that overall prevalence of HTN was higher in this part of rural area. Nearly half of the population was in the pre HTN. We noted a striking lack of awareness of the condition among and a suboptimal rate of control among those treated. These finding emphasize the public health importance of hypertension in the rural population and the likely increase in magnitude of this problem in India in the near future.